Tips for Writing an Effective Policy Brief for Health Programs - Nugroho, Heru Santoso Wahito; Sunarto, Sunarto; Suparji, Suparji; Rusdianti, Alfi (Health Notions, 2025)
Policy briefs are essential tools for communicating evidence-based recommendations in the field of public health. Given the complexity of health data and the sector’s broad societal impact, the ability to write clear, concise, and actionable policy briefs is vital. This paper outlines five fundamental components for producing high-quality health policy briefs: identifying target objectives and audiences, constructing coherent and succinct structures, using plain language with a focus on public impact, incorporating strong evidence and credible data sources, and applying accessible design principles. Emphasizing clarity and brevity, the paper highlights how policy briefs can bridge the gap between research and decision-making, ultimately contributing to more effective and responsive health policies. Keywords: policy brief; health sector; evidence-based recommendations